1993
DOI: 10.1021/bi00091a013
|View full text |Cite
|
Sign up to set email alerts
|

Importance of specific guanosine N7-nitrogens and purine amino groups for efficient cleavage by a hammerhead ribozyme

Abstract: Seven modified hammerhead ribozyme/substrate complexes have been prepared in which individual purine nitrogens, the guanine N7-, the guanine N2-, or the adenine N6-nitrogen, have been excised. The modified complexes were chemically synthesized with the substitution of a single 7-deazaguanosine (c7G), inosine (I), or nebularine (purine riboside, P) base analogue as appropriate for residues G5, G8, G12, A13, A14, or A15. Two of the base analogues, c7G5 and C7G8, occur in a 19-mer ribozyme, while the remaining th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
37
1

Year Published

1997
1997
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 67 publications
8
37
1
Order By: Relevance
“…In the ground-state structure of the hammerhead, the A13 nucleotide forms a nonstandard G{A pair with G8 (Fig+ 1)+ Pairing occurs via three hydrogen bonds, involving the exocyclic amino group and the N7 atom of A13 (Pley et al+, 1994;Scott et al+, 1995) (Fig+ 9)+ Removal of the base from A13 essentially abolishes catalysis, reducing the cleavage rate by almost 10 6 -fold (Table 1) (Peracchi et al+, 1996)+ Addition of adenine to near its solubility limit (;3 mM) gives a modest rescue of ;30-fold (Peracchi et al+, 1996)+ A survey of rescue for A13X is reported in Table 4+ Strikingly, many of the purines tested rival the rescuing efficiency of adenine, the base originally removed+ Compounds containing an exocyclic amino group, such as adenine or 2-aminopurine, or a keto group, such as hypoxanthine, and purine, which lacks exocyclic groups, all show similar values of k rescue + These observations with base rescue mirror the small effects observed previously with hammerhead constructs containing purine, 1-deazaadenosine, 3-deazaadenosine, 7-deazaadenosine, or isoguanosine substituted at position 13 (Fu & McLaughlin, 1992a;Slim & Gait, 1992;Fu et al+, 1993;Seela et al+, 1993;Bevers et al+, 1996;Seela et al+, 1998)+ Finally, the nucleosides adenosine and guanosine are surprisingly efficient in rescue at position 13 relative to the poor rescue observed with nucleosides at other positions (Tables 2-4; Peracchi et al+, 1996), suggesting that a greater freedom of motion at position 13 minimizes steric clashes of the nucleoside and backbone sugars+ FIGURE 7. The effects of probing a redundant functional interaction via site-directed mutagenesis (A) or base rescue (B), described by free energy reaction profiles+ A: For the wild-type ribozyme, the interaction in question is present in both the ground state and in the transition state+ Removal of the interacting functional group of the base ( Ⅲ ) destabilizes the ground state and the transition state to the same extent because, in this model, the remaining redundant interactions are sufficient to maintain the local structure+ Thus, the experiment does not reveal whether the functional group removed is involved in an interaction in the transition state (k ϭ k9)+ B: A base rescue experiment probing the same interaction+ Removal of the interacting functional group of the base is deleterious to rescue (k rescue .…”
Section: Rescue At Position 13supporting
confidence: 55%
See 1 more Smart Citation
“…In the ground-state structure of the hammerhead, the A13 nucleotide forms a nonstandard G{A pair with G8 (Fig+ 1)+ Pairing occurs via three hydrogen bonds, involving the exocyclic amino group and the N7 atom of A13 (Pley et al+, 1994;Scott et al+, 1995) (Fig+ 9)+ Removal of the base from A13 essentially abolishes catalysis, reducing the cleavage rate by almost 10 6 -fold (Table 1) (Peracchi et al+, 1996)+ Addition of adenine to near its solubility limit (;3 mM) gives a modest rescue of ;30-fold (Peracchi et al+, 1996)+ A survey of rescue for A13X is reported in Table 4+ Strikingly, many of the purines tested rival the rescuing efficiency of adenine, the base originally removed+ Compounds containing an exocyclic amino group, such as adenine or 2-aminopurine, or a keto group, such as hypoxanthine, and purine, which lacks exocyclic groups, all show similar values of k rescue + These observations with base rescue mirror the small effects observed previously with hammerhead constructs containing purine, 1-deazaadenosine, 3-deazaadenosine, 7-deazaadenosine, or isoguanosine substituted at position 13 (Fu & McLaughlin, 1992a;Slim & Gait, 1992;Fu et al+, 1993;Seela et al+, 1993;Bevers et al+, 1996;Seela et al+, 1998)+ Finally, the nucleosides adenosine and guanosine are surprisingly efficient in rescue at position 13 relative to the poor rescue observed with nucleosides at other positions (Tables 2-4; Peracchi et al+, 1996), suggesting that a greater freedom of motion at position 13 minimizes steric clashes of the nucleoside and backbone sugars+ FIGURE 7. The effects of probing a redundant functional interaction via site-directed mutagenesis (A) or base rescue (B), described by free energy reaction profiles+ A: For the wild-type ribozyme, the interaction in question is present in both the ground state and in the transition state+ Removal of the interacting functional group of the base ( Ⅲ ) destabilizes the ground state and the transition state to the same extent because, in this model, the remaining redundant interactions are sufficient to maintain the local structure+ Thus, the experiment does not reveal whether the functional group removed is involved in an interaction in the transition state (k ϭ k9)+ B: A base rescue experiment probing the same interaction+ Removal of the interacting functional group of the base is deleterious to rescue (k rescue .…”
Section: Rescue At Position 13supporting
confidence: 55%
“…In the hammerhead crystal structure, the base of G12 is positioned by four hydrogen bonds to G8 and A9 in the opposite strand and stacks onto the G10+1{C11+1 base pair (Pley et al+, 1994;Scott et al+, 1995Scott et al+, , 1996Murray et al+, 1998)+ Despite this, and in contrast with the rescue observed at the adjacent positions 9, 10+1, and 13, the hammerhead variant G12X is not rescued by the addition of exogenous guanine (Peracchi et al+, 1996)+ However, the solubility of guanine is low (;30 mM, which is 200-fold less than adenine and 2,000-fold less than cytosine)+ A more soluble guanine analog, 7-deazaguanine, gave a small rate increase with the G12X variant (threefold at 2 mM base), without increasing the wild type reaction (data not shown)+ The ability to observe some rescue with 7-deazaguanine is consistent with the efficient catalysis observed with a hammerhead construct containing 7-deazaguanosine at position 12 (Fu et al+, 1993), although the small extent of rescue precluded a detailed characterization+ Nevertheless, the use of soluble base analogs may sometimes allow the use of base rescue to probe additional abasic sites+…”
Section: Rescue At Position 12 By a Soluble Guanine Analogsupporting
confidence: 54%
“…Some experiments using exogenous 7-deazaguanine have been reported, as mentioned above (Peracchi et al 1996). Although ribozymes containing 7-deazaguanine at some residues other than G 10.1 (Fu et al 1993;Grasby et al 1995) and a ribozyme with N7-deazaguanine residue at 2 H -deoxy-G 10.1 (Wang et al 1999) have already been synthesized, to the best of our knowledge, this is the ®rst report of a cleavage reaction performed by an all-RNA ribozyme that contains 7-deazaguanine at G 10.1 . We ®rst examined R34 and 7-deaza-R34 in terms of k cat and K M under single-turnover conditions at 25 8C.…”
Section: Resultsmentioning
confidence: 99%
“…Transcription reactions were performed under standard conditions (37), except that RNA nucleotides 189 -236 were initiated with CpG to insert C189. RNA nucleotides 179 -188, containing different modified bases, were chemically synthesized (32)(33)(34)(35). Nucleotides 1-55 and 182-236 represent exons 1 and 2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Modified phosphoramidites for inosine (32), purine riboside (33), 2-aminopurine (2-AP) riboside (34), 7-deazaadenosine (c 7 A) (33), and phenylriboside (35) were synthesized according to the published protocol, except that the acetyl group was used for protection of 2-NH 2 functionality in the 2-AP riboside. These monomers were introduced into oligoribonucleotides by using standard coupling cycles, and the assembled oligonucleotides were purified by HPLC, as described earlier (36).…”
mentioning
confidence: 99%